Penurunan Tingkat Nyeri Bayi Saat Imunisasi Pentavalen Dengan Pemberian ASI Secara Menyusui - Permatasari, Indah; Ritanti, Ritanti (Jurnal Keperawatan, 2020)
Immunization pain is a stimulus that can cause trauma and changes affective response in the baby. Breastfeeding is the alternative strategies to reduce pain response due in invasive procedures. The aims of this study is to determine the effect of breastfeeding on infant pain levels when getting pentavalent immunization. This research using Randomized Controlled Trial design unblind, post-test design, with a sample of 70 healthy infants consisted of 34 respondents intervention group and 36 respondents of the control group were selected by random block technique. Breastfeeding intervention is given from two minutes before to 2 minutes after the immunization. In this study showed the pain level of intervention group is lower than the level of pain group (p = 0.000; Î± = 0.05). breast-fed infants when immunized can reduce the risk of severe pain by 80%, which compared to not breastfed infants. Further research on the effect of breast feeding for preterm infants pain response in invasive procedure.